Implementasi Video Pembelajaran Menggunakan Aplikasi CapCut Berbasis Problem-Based Learning dalam Pembelajaran Istima’ di SD Islam Cendikia Faiha Palembang - Wahyuni, Nur; Mukmin, Mukmin; Sabana, Rendi; Subillah, Aziz; Ramadona, Ramadona (Borneo Journal of Language and Education, 2025)
Listen ability is the initial skill that must be mastered by students because naturally humans first understand langue through hearing. However, the method used by educator is still teacher-centered and the limeted ude of learning media also affects the listening process of student. The learning media developed is a problem-based learning video. Learning using videos can insrease students understanding and student contentration on learning because of the combination of images, text and sound. Therefore, this study aims to develop and test the effectiveness of problem-based learning media based on problem based learning using the capcut application at Sd Islam Cendikia Faiha Palembang. This research uses the Research and Development method of the Borg and Gall model.The content / material expert validation questionnaire showed 80% results with a valid category and the media expert validation questionnaire obtained 80% esukt, both of which included a very valid category. The result showed that the student needs questionnaire reached 69.74% and the satisfaction questionnaire reached 76,07% both with the word valid category. The test between wo classes, namely the control class and the experimental class, showed a significant value of the control class pre test of 0,086, the control call post test of 0,100 and the significant value of experimental class pre test of 0,095 and the experimental post test of 0,241, so the date wa normally distributed. The homogeneity test obtained a value of 0,317 with the homogen category. Independent simple t-test significant value (2-tailed) 0,000 there is a significant defference in value between the control class and the experimental class. And the results of the clculation of the average value in the control class 38,39% including the less effective categoy while the average value in the experimental class reached 68,72% with a fairly effective category.